Promoting Thailand as Vineyard Tourism Destination for Foreign Tourists - Phattharasorn, Techita; Wichasin, Pimmada (Humanities and Social Sciences Nakhonsawan Rajabhat University Academic Journal, 2022)
The primary objective of this research was to promote Thailand as vineyard tourism destination for foreign tourists. The secondary objectives included (1) to develop the potentials and competitive capabilities of vineyard destinations (2) to develop vineyard tourism in Thailand by utilizing the concept of sustainability and the local community participation (3) to study the purchasing motivation and health benefits of wine affecting future purchase intention (4) to investigate the product factors and the demand of organizing activities and festivals affecting future tourism/purchase intention towards vineyards (5) to compare the future purchase intention of products in vineyards in terms of tourists’ demographic (6) to build the promotion plans of Thailand as vineyard tourism destination for foreign tourists. This research incorporated qualitative and quantitative researches. The research tools for data collection included the depth interview with key informants and the questionnaire with the samples of foreign tourists. The analyzing statistics were composed of descriptive statistics and inferential statistics multiple regression analysis, Independent sample t-test and one-way ANOVA. The findings of hypotheses testing revealed that The purchasing motivation factors of wine affecting future purchase intention consisted of (1) the purchasing intention of products in terms of souvenirs and the health benefits of the prevention of Parkinson disease. (2) the purchasing interest of fresh grapes in terms of health benefits of wine and the health benefits of the prevention of cold and sore throat. (3) the purchasing interest of wines in terms of digital medias such as online, social media and mobile phones and the health benefits of the prevention of mouth diseases. (4) the interest of activities in terms of wine fermentation time and the health benefits of the prevention of cold and sore throat. The product factors in vineyards affecting foreign tourists’ future purchase intention consisted of (1) the brand image and wine benefits in term of souvenir value (2) the interest of physical environments in vineyard in terms of light, color and sound at night (3) the demand of sensory benefits of selected wines (4) the interest of buildings in vineyard in terms of wine factory and (5) the weather condition 3.The demand factor of organizing activities and festivals affecting foreign tourists’ future tourism/purchase intention towards vineyards consisted of (1) winter festivals (2) grape harvesting festivals and (3) trade fairs The recommendation was derived from the integration of findings of qualitative and quantitative researches as follows: The development of the potentials of vineyard destinations should emphasize the green environment with the concept of research and development (R&D). The development of competitive capabilities should focus on strength of natural resources and beautiful scenery in line with the brand image, wine value, vineyard reputation, production and sales of favorite grape varieties and seasonal flowers, vegetables and fruits as the alternatives for customers. The guidelines of developing tourism network of vineyard tourism should utilize the concept of social, community and cultural sustainability and the local community participation as well as the incorporation of international and family administration of vineyard. The target marketing process should focus on Thai and foreign tourists and the product positioning of vineyard should emphasize the building of brand image and brand value of health benefits as well as the varieties of processed seasonal vegetables and fruits. 5.The promotion of Thailand as vineyard tourism destination for foreign tourists should be implemented through integrated marketing communication as well as local, national and international online, social media, and mobile marketing.